PHARMACOLOGICAL EXPERIMENTAL STUDY OF THE ANTI-DEPRESSANT EFFECT OF TOTAL SAIKOSAPONINS. - Liu, Yu; Cao, Chunmei; Ding, Haijun (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Chai Hu has the hepato-protective, choleretic, anti-tussive, analgesic, anti-inflammatory, anti-viral, hypotensive, hypolipidemic, and anti-tumor pharmacological effects. In this study, the objective of this paper was to study the anti-depressant effect of total saikosaponins. Materials and Methods: Total saikosaponins were extracted by reflux method, and were identified by thin layer chromatography (TLC). The anti-depressant effect of total saikosaponins was investigated in vitro by tail suspension test, forced swimming test, and reserpine antagonism test in mice. Results: Two times of reflux extraction, temperature of 70℃, and extraction time of 4hrs, for each extraction could improve the yield of saikosaponins. Each treatment group (100, 200, and 300 mg/kg), could significantly shorten the immobility time of mice in the tail suspension test in a somewhat dose-dependent manner. The total saikosaponins antagonized the reserpine-induced akinesia, and ptosis in mice. Conclusion: Total saikosaponins have an anti-depressant effect.